Vapor-fed microfluidic hydrogen generator1. Issue 10 (21st May 2015) - Modestino, M. A.; Dumortier, M.; Hosseini Hashemi, S. M.; Haussener, S.; Moser, C.; Psaltis, D.
<x xml:space="preserve">Abstract</x> Water-splitting devices that operate with humid air feeds are an attractive alternative for hydrogen production as the required water input can be obtained directly from ambient air.